Effect of adding different levels of biochar and cow manure on some yield characteristics of soybean (Glycine max L.) and some physical properties of the soil - ميهوب, أمجد; ديفانا يوسف,; منى بركات , (Latakia University Journal -Biological Sciences Series, 2024)
The study was carried out in Sheikh Badr area of Tartous Governorate for the agricultural season 2023, to study the effect of adding different levels of biochar and cow dung on some productive characteristics of soybean crop and some physical properties of the soil.The experiment was designed on the basis of randomized complete blocks with ten treatments with three replicates of each treatment, no addition, mineral fertilizer treatment. (15 tons/ha-30 tons/ha) of cow manure, (2%-4% of soil by weight) biochar, (15 t/ha of cow dung with 2% of soil by weight biochar), (15 t/ha of cow dung with 4% of soil by weight biochar), (30 t/ha of cow dung with 2% of soil by weight biochar), (30 t/ha of (30 tons/ha of cow dung with 2% of soil and biochar weight) (30 tons/ha of cow dung with 4% of soil and biochar weight). The study included several yield attributes such as (number of pods on the plant, number of seeds per pod the number of pods on the plant, the number of seeds in the pod, the weight of 100 seeds), and several physical soil properties such as (porosity Porosity, pore size distribution, bulk density): The biochar treatment outperformed 4% of the soil by weight and cow dung 30 tons/hectare in increasing the number of pods on the plant and increasing the number of seeds in the pods. and increase the number of seeds per pod, and increase the weight of 100 seeds; treatment with biochar contributed treatment with biochar 4% of soil by weight and cow manure 30 tons/hectare contributed to lowering the bulk density and increasing the total porosity and increased total , aerobic porosity and decreased capillary porosity.